The Role of Human Resources Management Practices In The Realization of Organization’s Competitive Advantage - SINHA, DR.RAJENDRA (The journal of contemporary issues in business and government, 2021)
The present study identified role of human resource management in the realization of competitiveness in industrial organizations and has focused primarily on some important issues related to human resource management, selection, training, motivating, attracting, employing, evaluating employees, and the setting of salaries, fees and rewards and the realization of competitiveness among business organizations. This paper has undergone the evolution of HRM from past to present which will be discussed in a theoretical concept. Then the role of human resources for organizations to gain competitive advantage and the innovations in HRM in the 21st century will be analyzed in a strategic view. Data were drawn from a sample of two industrial business organizations in the city of Amman. The study results showed that there is a significance relationship between the factors such as training, motivating, attracting, employing, evaluating employees, and the setting of salaries, fees and rewards of employees and workers and the realization of competitiveness among industrial business organizations. And this result is consistent with the outcome of previous studies.